Risk factors of central nervous system relapse in mantle cell lymphoma. Issue 9 (September 2013) - Conconi, Annarita; Franceschetti, Silvia; Lobetti-Bodoni, Chiara; Stathis, Anastasios; Margiotta-Casaluci, Gloria; Ramponi, Antonio; Mazzucchelli, Luca; Bertoni, Francesco; Ghielmini, Michele; Gaidano, Gianluca; Cavalli, Franco; Zucca, Emanuele
Abstract: Central nervous system (CNS) relapse has not been extensively studied in mantle cell lymphoma (MCL). We retrospectively analyzed the risk factors and pattern of CNS relapse in consecutive patients with MCL. We identified 142 cases of MCL treated from 1980 to 2011. Median age at diagnosis was 68 years; 82% of patients had advanced stage; extranodal disease was reported in 89% of cases and high serum lactate dehydrogenase (LDH) in 40%. Fourteen patients (10%) did not receive treatment at diagnosis. Chemotherapy was administered to 125 patients (88%), in 21 cases (15%) including drugs penetrating into the CNS or given intrathecally; 49 patients (35%) had rituximab. Ten patients had front-line autologous transplant. After a median follow-up of 7.9 years, CNS relapse occurred in 11 cases (7.8%) at a median of 13.8 months. Actuarial risk of CNS relapse was higher in patients with elevated LDH ( p = 0.002), higher International Prognostic Index (IPI) score ( p = 0.018) and blastoid histology ( p < 0.0001). Blastoid histology retained significance at multivariate analysis. Median survival after CNS relapse was 6.3 months. No front-line treatment reduced the risk of CNS relapse. Our analysis confirms the poor outcome of MCL after CNS relapse and may allow the identification of patients needing prophylaxis of CNS relapse.